Community Participation In Village Fund Management In Banyuanyar Village, Boyolali Regency - Ellectrananda Lusia Indrastuti (IHSA Institute, 2022)
Community participation is one of the factors that influence the success of development programs and rural community development. Community participation is needed to realize village development in accordance with the needs of the village itself. Community participation does not only involve the community in making decisions in every development program, but the community is also involved in identifying problems and potentials that exist in the community. Without community participation every development activity will fail. Likewise with regard to community participation in the use and management of village funds, this involvement is important so that the use and management can be more targeted and the benefits will be more impactful. However, what happened in Banyuanyar Village, Ampel District, Boyolali Regency in terms of the use and management of village funds was still minimal related to community involvement or participation. This affects community support for various programs that will be run using village funds. This of course would violate the requirements in managing village funds that have been regulated in Law No. 23 of 2014 which already regulates how to manage and use village funds. There are several factors that affect the level of community participation in the management of village funds such as the lack of socialization from the village government regarding the village fund program so that people do not understand about the village fund program, which makes the community less participating. In addition, the education factor for the people of Banyuanyar Village, Ampel District, Boyolali Regency is still lacking, so it is difficult for people to understand all the activities carried out by other people in the community.